Tracer study to assess the employability of graduates and quality of a nursing program: A descriptive cross-sectional survey - Veronica M. Dzomeku; Abigail Kusi Amponsah; Edward A. Boateng; John Antwi; Philemon Adoliwine Amooba; Puoza Deo Gracious; Jerry Armah; Victoria Bam (Elsevier, 2024)
Background: Contribution of nursing is crucial for Universal Health Coverage and achieving Sustainable Development Goal 3. Tracer studies help evaluate accountability and demonstrate the impact of nursing educational institutions in a highly competitive job market. The study aimed at assessing the employability of nursing graduates, and perceived quality of the nursing program they pursued in a public tertiary institution in Ghana. Method: The study employed a descriptive cross-sectional survey. One hundred and ten (110) nursing graduates responded to a web-based survey. The data were gathered using a customized questionnaire based on the Tarlac State University Graduates Tracer Questionnaire. Data were collected via google forms, and analyzed using descriptive and inferential statistics. Results: Majority of the participants were females (n = 64, 58.2 %). Most of the participants had completed a Bachelor's degree at the tertiary institution (n = 101, 91.8 %). A significant proportion of the participants were gainfully employed during the study period (n = 102, 92.7 %) with majority of them working in the public sector (n = 81, 79.4 %). The quality of the diploma or degree program obtained was rated good in most of the areas by over 50 % of the participants. There was no statistically significant association between the highest educational qualification of participants and their perceptions on the quality of the nursing program. Conclusion: There is the need to conduct this kind of tracer study on a regular basis to keep track of graduate's progress and obtain feedback on the quality of programs being offered so as to meet the ever-changing needs of society.